Sepsis and major abdominal surgery lead to flaking of the endothelial glycocalix - Steppan, Jochen; Hofer, Stefan; Funke, Benjamin; Brenner, Thorsten; Henrich, Michael; Martin, Eike; Weitz, Jürgen; Hoffmann, Ursula; Weigand, Markus A. (Journal of surgical research, 2011)
Background - Recent evidence suggests that the endothelial glycocalix plays an important role in lethal outcomes following sepsis. We therefore tested if the endothelial glycocalix is shed in patients with sepsis compared with patients after major abdominal surgery and healthy volunteers. - Material and Methods - A total of 150 individuals were tested for levels of inflammatory markers (intercellular adhesion molecule-1 [ICAM-1], vascular cell adhesion molecule-1 [VCAM-1], interleukin-6 [IL-6]) and glycocalix markers (syndecan-1, heparan sulfate). Three groups consisted of patients with severe sepsis or septic shock, patients after major abdominal surgery without systemic inflammatory response syndrome, and healthy volunteers. Blood was drawn, at the time of diagnosis or surgery, and 6, 24, and 48h later. We correlated these markers to each other and to clinically used inflammation markers. - Results - Levels of inflammatory markers were markedly higher in patients with sepsis compared with patients after major abdominal surgery and healthy volunteers. After major abdominal surgery, glycocalix markers in human plasma were at levels comparable to patients with sepsis. In patients with sepsis, levels of IL-6 correlated with syndecan-1, ICAM-1, VCAM-1, and lactate, while ICAM-1 furthermore correlated with CRP and lactate levels. - Conclusion - High levels of glycocalix markers indicated that significant flaking of the endothelial glycocalix occurred in patients with sepsis, and to a lesser extent in patients after major abdominal surgery. This novel finding could explain the nonspecific capillary leaking syndrome of patients with sepsis and after major abdominal surgery, and may identify new targets for treating those patient populations.
Online verfügbar 20 Mai 2009
Gesehen am 21.10.2022
Ursula Hoffmann ist fälschlich als Ursula Hofmann geschrieben